Nationalist Politics and the Double Movement: The Problem of Legitimacy in Neoliberal States - Blad, Cory (Conference Papers – American Sociological Association, 2013)
This paper argues that the contemporary efficacy of nationalist politics is a strategic response to neoliberal conditions of state legitimation. Using the double movement as a theoretical framework, I argue that neoliberalism alters the policy alternatives available to state actors by reducing the viability of economic protectionist initiatives once dominant in the embedded liberal era. This policy capacity reduction inhibits some of the key means for state legitimation (e.g., public spending, regulatory protectionism), which exacerbate the negative effects of capitalist liberalization. As national populations view the state as unwilling or unable to mitigate economic adversities or provide traditional socio-economic services, significant potential exists for a delegitimation of state actors and institutions. In response, neoliberal state actors have gravitated toward an increasingly cultural rhetoric of nationalism as a means to maintain popular legitimacy. This shift goes beyond simple political power struggles - in accordance with the double movement framework, systemic global capitalism requires legitimate state authority to ensure both local stability and sustained capital accumulation. Neoliberal ideology, however, discourages traditional means of state legitimation. A Polanyian examination of this ironic condition offers a structural explanation for the increased efficacy of nationalist politics; however, it also raises serious questions about the sustainability of this legitimation strategy.
Sociology
Keywords: double movement; globalization; nationalism; neoliberalism; state legitimation

Economic support personal networks of rural entrepreneurships - Cid-Aguayo, Beatriz E.; Sandoval-Nazal, Daniel; Carrasco, Juan Antonio (Conference Papers – American Sociological Association, 2013)
The Polanyian discussion about the embeddedness of the economy in social relations, finds a new stream through the social network analysis, from which is possible to map the cooperation relations that underlie economic ones. From the latter, this article shows the analysis of nine family-based economic entrepreneurships linked to a cooperative of services and agrofood products. Through personal networks analysis we mapped and highlighted the diversity of collaborations, monetary and non-monetary exchanges the entrepreneurships perform with their networks. In consequence, we characterized the support networks identifying the different economic exercises that take part in relation to the entrepreneurships. By this way, we accounted some relevant aspects such as the formality or informality condition, the entrepreneurships level, the networks' cohesion and the types of exchange, among other issues.
Sociology
Keywords: embeddedness; rural entrepreneurships; social networks